Le champs lexico-sémantique de la notion «L’amour» (au matériel du roman de Gustave Flaubert «L’éducation sentimentale») - Khaichevska, Tetiana M.; Mirchuk, Tetiana; Хайчевська, Тетяна Миколаївна; Мірчук, Тетяна (Національний університет "Острозька академія", 2017)
Ces derniers temps l’attention particulière des linguistes portent sur les études des liens des faits linguistiques effectuées à la base des œuvres littéraires: les liens objectifs existant entre les faits séparés de la langue et les moyens linguistiques unissant ces faits. L’analyse sémantique des unités lexicales et de leurs fonctions stylistiques dans un texte littéraire s’inscrivent dans le cadre de la théorie sémasiologique générale. Cet article est consacré à l’étude des particularités linguistiques de la réalisation de la notion «amour» dans le roman de G. Flaubert «L’éducation sentimentale». En analysant le texte du roman, on a déterminé un corpus de moyens linguistiques réuni dans le champ lexico-sémantique de l’amour qui constituent la présentation explicite et implicite de ce sentiment. Dans cette recherche, nous nous sommes basés sur l’interprétation du texte littéraire à travers le champ lexico-sémantique. Une telle méthode nous aidera à préciser non seulement des raisons objectives, qui influencent le choix du lexique par l’auteur, mais à comprendre son opinion aussi. Дана стаття присвячена вивченню лінгвістичних особливостей репрезентації поняття «кохання» у романі Гюстава Флобера «Сентиментальне виховання» зокрема дослідженню його лексико-семантичного поля. Гюстав Флобер є одним із найвідоміших французьких письменників, який описував природу людських почуттів, тому ми обрали один з його романів, який є менш дослідженим з точки зору лінгвістики і водночас цікавим матеріалом для наукової розвідки. Метою даного дослідження є семантичний та функціональний аналіз лексики, що пов'язаний з вираженням різних аспектів кохання. Проаналізувавши текст роману, було визначено сукупність мовних засобів, які формують лексико-семантичне поле (експліцитне й імпліцитне вираження) поняття «кохання». This article is devoted to the investigation of linguistic peculiarities of representation of the notion «love» in the novel «Sentimental Education» by Gustave Flaubert, including the research of corresponding lexico-semantic fi eld. This writer is one of the most famous French authors who described human emotions and we choose this novel because it is not studied enough. The purpose of this research is semantic and functional analysis of the vocabulary associated with different aspects of love. Having analyzed the text of the novel, the complex of linguistic means constituting the lexico-semantic fi eld (explicit and implicit expression) of the notion «love» was defi ned. The results of the study prove that the nucleus of the lexico-semantic fi eld under study is a noun amour and its derivatives (over 160 examples of word usage), the central part comprises such lexical units as adoration adoration, passion passion, and its periphery includes lexical units liaison relationship, caprice caprice, baiser a kiss, dévouement commitment. The sequence of lexical units according to the degree of semantic proximity to the basic meaning was also defi ned. The research revealed permanent connection between lexical units that refl ect explicit and implicit realizations of the notion of love, in particular by adjectives romantique, joyeux, fort, nouns affection, tendresse, admiration and an adverb profondément. The author’s vision of «love» in the novel is characterized by certain symbols, that is why such stylistic fi gures as hyperbole and rhetorical questions play an important role in the interpretation of the text
Лексико-семантичне поле поняття "Кохання" (на матеріалі роману Гюстава Флобера "Виховання почуттів")
Lexico-semanic field of the notion « Love » (on the material of the novel « Sentimental education by Gustave Flaubert)
Keywords: le champ lexico-sémantique; l’unité lexicale; la notion «amour»; le noyau du champ lexico-sémantique; la proximité sémantique; лексико-семантичне поле; лексична одиниця; поняття «кохання»; ядро лексико-семантичного поля; семантична близькість; лексико-семантичне поле; лексична одиниця; поняття «кохання»; ядро лексико-семантичного поля; семантична близькість